Experimental and numerical analysis of RC structure with two leaf cavity wall subjected to shake table - Onat, Onur; Lourenco, Paulo B.; Kocak, Ali (TECHNO-PRESS, 2015)
This paper presents finite element (FE) based pushover analysis of a reinforced concrete structure with a two-leaf cavity wall (TLCW) to estimate the performance level of this structure. In addition to this, an unreinforced masonry (URM) model was selected for comparison. Simulations and analyses of these structures were performed using the DIANA FE program. The mentioned structures were selected as two storeys and two bays. The dimensions of the structures were scaled 1: 1.5 according to the Cauchy Froude similitude law. A shake table experiment was implemented on the reinforced concrete structure with the two-leaf cavity wall (TLCW) at the National Civil Engineering Laboratory (LNEC) in Lisbon, Portugal. The model that simulates URM was not experimentally studied. This structure was modelled in the same manner as the TLCW. The purpose of this virtual model is to compare the respective performances. Two nonlinear analyses were performed and compared with the experimental test results. These analyses were carried out in two phases. The research addresses first the analysis of a structure with only reinforced concrete elements, and secondly the analysis of the same structure with reinforced concrete elements and infill walls. Both researches consider static loading and pushover analysis. The experimental pushover curve was plotted by the envelope of the experimental curve obtained on the basis of the shake table records. Crack patterns, failure modes and performance curves were plotted for both models. Finally, results were evaluated on the basis of the current regulation ASCE/SEI 41-06.
Keywords: reinforced concrete; shake table; finite element method; infill wall; pushover; PUSHOVER ANALYSIS; EARTHQUAKE; BUILDINGS; MASONRY; PERFORMANCE; Engineering